2020
DOI: 10.3390/foods9121866
|View full text |Cite
|
Sign up to set email alerts
|

Use of Turkey Meat Affected by White Striping Myopathy for the Development of Low-Fat Cooked Sausage Enriched with Chitosan

Abstract: The main objective of this research was the development of a healthy meat product from turkey meat with white striping myopathy. The effect of adding different proportions of chitosan on the qualitative characteristics, sensory acceptance, and stability of cooked sausages during storage was studied. Three treatments were elaborated (control, 1.5% chitosan, and 3% chitosan), stored for 56 days, and characterized in terms of chemical composition, texture profile analysis, drip and pressure loss analysis, and sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
(146 reference statements)
0
5
0
Order By: Relevance
“…Aldehydes are secondary products of fatty acid oxidation [53]. According to the literature, aldehydes are better indicators of lipid oxidation than other volatile substances [54]. In this study, aldehydes were the largest established VOC group in broiler meat affected by WB together with WS.…”
Section: Discussionmentioning
confidence: 51%
“…Aldehydes are secondary products of fatty acid oxidation [53]. According to the literature, aldehydes are better indicators of lipid oxidation than other volatile substances [54]. In this study, aldehydes were the largest established VOC group in broiler meat affected by WB together with WS.…”
Section: Discussionmentioning
confidence: 51%
“…Improvements in emulsion stability and cooking loss due to the addition of CMs may have led to an increase in hardness values. Previous studies reported that the addition of chitosan to emulsified sausages increased hardness and gumminess, which was consistent with our results (Carvalho et al ., 2020). In particular, DeP, DeM and DeA caused notable changes in hardness and gumminess, with greater changes compared to DeH, which is closest to chitosan.…”
Section: Resultsmentioning
confidence: 99%
“…Lipid oxidation is one of the most critical factors that affect the quality deterioration of meat products. It can lead to the loss of fatty acids, decreased sensory quality and nutritional value, and the production of harmful substance MDA (Carvalho et al ., 2020). The inhibition ability of PHPR03 on lipid oxidation of ground pork stored at 4 °C for 7 days was evaluated by measuring TBARS (Fig.…”
Section: Resultsmentioning
confidence: 99%